( 5 2 + 6 4 3 ) 3 / 2 − ( 5 2 − 6 4 3 ) 3 / 2 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We first find the square roots, making the Ansatz 5 2 + 6 4 3 = a + b 4 3 . Squaring both sides we want a 2 + 4 3 b 2 = 5 2 and 2 a b = 6 , with the positive solution a = 3 , b = 1 . Thus 5 2 + 6 4 3 = 3 + 4 3 . Likewise, 5 2 − 6 4 3 = − 3 + 4 3 . Using the Binomial Theorem, we find ( 5 2 + 6 4 3 ) 3 / 2 − ( 5 2 − 6 4 3 ) 3 / 2 = ( 3 + 4 3 ) 3 − ( − 3 + 4 3 ) 3 = 3 3 + 3 × 3 2 4 3 + 3 × 3 × 4 3 + 4 3 4 3 − ( − 3 3 + 3 × 3 2 4 3 − 3 × 3 × 4 3 + 4 3 4 3 ) = 2 × 3 3 + 2 × 3 2 × 4 3 = 8 2 8 .
Why isn't it possible that a = 1 , b = 3 ?
Why can't 5 2 − 6 4 3 be equal to ( 3 − 4 3 ) 2 ? How can you be certain that it is equal to ( 4 3 − 3 ) 2
Log in to reply
Well, it's equal to both ;)
Log in to reply
Won't it affect the answer? Here's what I mean,
Case 1: ( 3 + 4 3 ) 3 − ( 3 − 4 3 ) 3 = 1 4 0 4 3
Case 2: ( 4 3 + 3 ) 3 − ( 4 3 − 3 ) 3 = 8 2 8
So we have two answers. Can you contradict the first case somehow? Thanks.
Log in to reply
@Rishik Jain – I answered the question you asked: 5 2 − 6 4 3 = ( 3 − 4 3 ) 2 = ( 4 3 − 3 ) 2 . Now 5 2 − 6 4 3 is non-negative, by definition, so that it is 4 3 − 3 .
Log in to reply
@Otto Bretscher – Sir, in the question, it is not of the form of square roots.
Log in to reply
@Rishik Jain – Wow, you are persistent ;)
For a positive x you have, by definition, x 3 / 2 = x 3
Log in to reply
@Otto Bretscher – Ok, Thanks for clarifying the doubt.
Log in to reply
@Rishik Jain – In particular, ( − 8 ) 2 = 8 .
Remember that for real numbers, x 2 = ∣ x ∣ , and not just x .
Problem Loading...
Note Loading...
Set Loading...
Let y denote the value of the expression in question, and let x = ( 5 2 + 6 4 3 ) 1 / 2 − ( 5 2 − 6 4 3 ) 1 / 2 , and we hope to find a relationship between x and y .
By squaring the equation x = ( 5 2 + 6 4 3 ) 1 / 2 − ( 5 2 − 6 4 3 ) 1 / 2 , (recall the identity, ( a − b ) 2 = a 2 + b 2 − 2 a b ) we have
x 2 x = = = = = = [ ( 5 2 + 6 4 3 ) 1 / 2 − ( 5 2 − 6 4 3 ) 1 / 2 ] 2 [ ( 5 2 + 6 4 3 ) + ( 5 2 − 6 4 3 ) − 2 ( 5 2 + 6 4 3 ) ( 5 2 − 6 4 3 ) ] [ ( 5 2 + 6 4 3 ) + ( 5 2 − 6 4 3 ) − 2 5 2 2 − 6 2 ( 4 3 ) ] [ 2 ( 5 2 ) − 2 3 4 2 ] 3 6 6
Note that we take the positive x only because x is 5 2 + 6 4 3 > 5 2 − 6 4 3 > 0 ⇒ ( 5 2 + 6 4 3 ) 1 / 2 > ( 5 2 − 6 4 3 ) 1 / 2 ⇒ x > 0 .
Similarly, raising both sides of the equation x = ( 5 2 + 6 4 3 ) 1 / 2 − ( 5 2 − 6 4 3 ) 1 / 2 by 3, (recall the identity, ( a − b ) 3 = a 3 + b 3 − 3 a b ( a − b ) ) we have
x 3 6 3 2 1 6 y = = = = ( 5 2 + 6 4 3 ) 3 / 2 − ( 5 2 − 6 4 3 ) 3 / 2 − 3 ( 5 2 + 6 4 3 ) ( 5 2 − 6 4 3 ) ⋅ x y − 3 5 2 2 − 6 2 ⋅ 4 3 ⋅ 6 y − 1 8 3 4 2 8 2 8